DFT study on the oxygen titanium porphyrin as sustainable cyclic catalyst for water splitting. (26th July 2019) - Yu, Hong-Xia; Mu, Hui-Min; Zhu, Dong-Ran; Zhang, Yong; Wang, Xiao-Chun; Xiao-An Zhang, Sean
Abstract: With global resource shortage and deterioration of ecological environment, the research and development of clean and renewable energy is of vital importance. Using first-principles calculations, we firstly study water splitting catalyzed by metal based biomolecule porphyrin (MPP) (M = Mg, Ba, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, and Zn). Among all the systems, after releasing electron, TiPP is the most effective catalyst for H2 O splitting. TiPP and the remainder O atom form the very stable structure OTiPP. The H2 O + OTiPP can release electron with the 6.76 eV potential barrier. The releasing electron process of porphyrin can be easily realized under the effect of solar energy by experiment study. After releasing electron, OTiPP can effectively catalyze the dissociation of H + from H2 O in an exothermic process. The desorption of O atom is an endothermic process with 0.72 eV barrier. The H2 O + OTiPP system can readily return to its original state OTiPP, in other word, the OTiPP can be a sustainable cycling catalyst for water splitting under the effect of potential barrier transfer. The whole catalytic process is remarkable clean without any pollution. This method may open up new avenues for the development of future clean energy and extraordinary biomimetic photosynthesizers. Graphical abstract: Image 1 Highlights: The TiPP can efficiently catalyze the H2 O splitting to form the stable OTiPP. The OTiPP is the high-efficiency and recycled catalyst for H2 O splitting. The potential barrier transfer effect is the point for the OTiPP catalytic progress.